Tuberous Sclerosis Complex : A Case Report - Rofiq, Aunur; Setyowati, Lita; Nugrahani, Aninda Fitri (Universitas Muhammadiyah Malang, 2019)
Tuberous Sclerosis Complex (TSC) is an autosomal dominant inherited neurocutaneous disorder. Tuberous Sclerosis Complex is caused by mutations in tumor suppressor gene (TSC), both TSC1 and TSC2. In approximately two-thirds of cases neither parent has signs of TSC and the disease is caused by a de novo mutation. Tuberous Sclerosis Complex is classically identified by the Vort's triad in the presence of angiofibroma, mental retardation, and epilepsy. A 17-year-old woman with a major complaint of a facial bump that appeared at birth and got bigger when she reached puberty. There are white patches on the patient's body from birth. On the scalp obtained the presence of skin color plaque, while at the back and right knee obtained shagreen patch. Patientwas diagnosed with epilepsy and mental retardation by the pediatric department. No family history has the same complaints as patient. Histopathologic examination of facial bumps taken by shaving biopsy suggests the presence of hemangiomas. Based on the clinical diagnostic criteria from International Tuberous Sclerosis Complex Consensus Conference 2012, the patient meets two major criteria, macular hypopigmentation and shagreen patch so it is included in